2019
DOI: 10.1371/journal.pntd.0007490
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination against the digestive enzyme Cathepsin B using a YS1646 Salmonella enterica Typhimurium vector provides almost complete protection against Schistosoma mansoni challenge in a mouse model

Abstract: Schistosoma mansoni threatens hundreds of millions of people in >50 countries. Schistosomulae migrate through the lung and adult worms reside in blood vessels adjacent to the intestinal mucosa. Current candidate vaccines aren’t designed to elicit a mucosal response. We have repurposed an attenuated Salmonella enterica Typhimurium strain (YS1646) to produce such a vaccine targeting Cathepsin B (CatB), a digestive enzyme important for parasite survival. Promoter-Type 3 secretory signal pairs were screened for pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 57 publications
3
30
1
Order By: Relevance
“…RNA interference studies demonstrate that when cathepsin B transcript levels are suppressed resulting worms show significant growth retardation compared to control parasites ( 9 ). By targeting cathepsin B, reduced egg fitness has been demonstrated by our group ( 10 ), and parasite anti-fecundity has also been seen in other flukes ( 11 ).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…RNA interference studies demonstrate that when cathepsin B transcript levels are suppressed resulting worms show significant growth retardation compared to control parasites ( 9 ). By targeting cathepsin B, reduced egg fitness has been demonstrated by our group ( 10 ), and parasite anti-fecundity has also been seen in other flukes ( 11 ).…”
Section: Introductionmentioning
confidence: 74%
“…The following day, the eggs present in these tissues were counted by microscopy and adjusted per gram of tissue. Burden reductions were calculated as previously described (12)(13)(14):…”
Section: Schistosoma Mansoni Challengementioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was a limitation concerning our results, considering natural variation in worm recovery, egg count and liver lesions. Alternative more powerful delivery systems could improve vaccination results [ 52 ]. The candidates’ immunogenicity was monitored by ELISA and it was observed that SmTNP triggered high specific IgG antibody levels in vaccinated, non-infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the past several decades, over 100 schistosome antigens have been advanced as possible vaccines [ 63 , 65 ], and recently developed approaches provide an avenue to identify and test additional candidate molecules for protective efficacy [ 66 , 67 , 68 ]. Indeed, many proteins are exposed at, or released from, the parasite–host interface so many other possibilities remain for potential vaccine exploitation.…”
Section: Schistosomiasismentioning
confidence: 99%